How and for whom abusive supervision influences organizational citizenship behavior: the roles of burnout and workplace friendship - KARATAŞ GÜMÜŞTAŞ, NİLGÜN (My University, 2024)
Purpose – Although many studies have investigated the link between abusive supervision and employee organizational citizenship behavior (OCB), most of them have been performed in isolation, resulting in inconsistent findings and a lack of a systematic structure for understanding how abusive supervision affects OCB. Building on the conservation of resources theory, this study aims to investigate the impact of abusive supervision on OCB through the mediating role of burnout. Additionally, the moderating influence of workplace friendship on the link between abusive supervision and burnout was examined. Design/methodology/approach – We used data from a two-wave survey of 316 employees with a time interval of 4 weeks. We conducted a mediated moderation analysis to test our model using PROCESS (Hayes, 2013), a statistical macro for SPSS, to examine moderatedmediation models’ direct and indirect effects. Findings – The findings revealed that burnout completely mediated the association between abusive supervision and OCB. Additionally, workplace friendships strengthen employees’ social networks, providing them with increased resources and support when facing abusive supervision compared to those lacking such friendships. The results have both theoretical and practical implications, which are discussed. Originality/value – First, this study examined the moderating role of workplace friendship and the mediating role of burnout in the relationship between abusive supervision and OCB. This is a novel contribution to the literature, as previous research has not examined these factors. Previous research has shown that abusive supervision can lead to decreased effort, but the mechanisms that affect job performance have attracted relatively little attention. Keywords Abusive supervision, Burnout, Organizational citizenship behavior, Workplace friendship
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; İşletme; Kitle İletişimi ve Araçları; Social Sciences and Humanities; Sociology; Management; Mass Communications and Mass Media; Sosyal Bilimler (SOC); Ekonomi ve İş; Sosyal Bilimler Genel; İŞLETME; İLETİŞİM; SOSYAL BİLİMLER, İNTERDİSİPLİNER; Social Sciences (SOC); ECONOMICS & BUSINESS; SOCIAL SCIENCES, GENERAL; BUSINESS; COMMUNICATION; SOCIAL SCIENCES, INTERDISCIPLINARY; İletişim; Sosyal Bilimler ve Beşeri Bilimler; Strateji ve Yönetim; Teknoloji ve İnovasyon Yönetimi; Communication; Social Sciences & Humanities; Strategy and Management; Management of Technology and Innovation; Abusive supervision; Burnout; Organizational citizenship behavior; Workplace friendship